Characterization and functionalization of zirconia membranes manufactured by aqueous tape casting - Silva, Bernardo Araldi da (2019)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Engenharia Química, Florianópolis, 2019